2017
DOI: 10.1016/j.artres.2017.02.002
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive evaluation of varying pulse pressures in vivo using brachial sphymomanometry, applanation tonometry, and Pulse Wave Ultrasound Manometry

Abstract: The routine assessment and monitoring of hypertension may benefit from the evaluation of arterial pulse pressure (PP) at more central locations (e.g. the aorta) rather solely at the brachial artery. Pulse Wave Ultrasound Manometry (PWUM) was previously developed by our group to provide direct, noninvasive aortic PP measurements using ultrasound elasticity imaging. Using PWUM, radial applanation tonometry, and brachial sphygmomanometry, this study investigated the feasibility of noninvasively obtaining direct P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 49 publications
0
9
0
Order By: Relevance
“…To monitor the pulse wave, pressure sensors are attached at a suitable place on the neck, arm, and wrist by medical tape to monitor the aorta, brachial, and radial arteries, respectively (inset of Figure a). As shown in Figure a, periodic pulse waveforms are acquired from the corresponding locations, indicating typical waveforms for the aorta and radial arteries . The aortic pulse waveforms also exhibit representative points, from which three parameters including round‐trip travel time, systolic duration, and the aortic augmentation index can be extracted (Figure S13, Supporting Information) .…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…To monitor the pulse wave, pressure sensors are attached at a suitable place on the neck, arm, and wrist by medical tape to monitor the aorta, brachial, and radial arteries, respectively (inset of Figure a). As shown in Figure a, periodic pulse waveforms are acquired from the corresponding locations, indicating typical waveforms for the aorta and radial arteries . The aortic pulse waveforms also exhibit representative points, from which three parameters including round‐trip travel time, systolic duration, and the aortic augmentation index can be extracted (Figure S13, Supporting Information) .…”
Section: Resultsmentioning
confidence: 97%
“…As shown in Figure 4a, periodic pulse waveforms are acquired from the corresponding locations, indicating typical waveforms for the aorta and radial arteries. [26,27] The aortic pulse waveforms also exhibit representative points, from which three parameters including round-trip travel time, Figure 3. a) Schematic illustration of the pressure sensor for monitoring human vital signs.…”
Section: Monitoring Of Arterial Pulse Waveformsmentioning
confidence: 99%
“…Other studies investigating biomechanical changes of vessel wall due to age and hypertension have included between 8 and 30 participants in ultrasound studies and between 8 and 21 participants in MRE studies. 17,18,21,23,24,27 Participants Inclusion criteria for healthy participants were an age of at least 18 years and absence of cardiovascular risk factors (ie, arterial hypertension, hyperlipidemia, diabetes, active smoking, and/or obesity with a body mass index >30 kg/m 2 ). Inclusion criteria for patients were a history of hypertension and current intake of antihypertensive medication.…”
Section: Methodsmentioning
confidence: 99%
“…The other method is to optimize the quality of the pressure and flow waveform of arteries through local pulse wave velocity (PWV) using ultrasound imaging. Li et al measured aortic waveform through ultrasound imaging to correct pressure, and demonstrated that the peak of the forward wave of the radial pulse wave was related to the inflection point of aortic pulse wave in the healthy subjects and prehypertension patients, which represented the beginning of pressure increase [24].…”
Section: ) Multichannel Signalmentioning
confidence: 99%
“…With the development of sensor technologies, flexible sensors have been used to record radial pulse waves [17,18]. In addition, some researchers have employed multi-sensor fusion methods including multichannel signal fusion [19][20][21][22][23][24], and array signal fusion [20,[25][26][27], to obtain rich information related to the cardiovascular system from radial pulse waves. However, comprehensive analysis of radial parameters, morphological changes, and clinical applications has not been reported.…”
mentioning
confidence: 99%